The genealogy of Maria de Aguilar: evidence of admixture in the early Spanish Colony in Costa Rica - Morera, Bernal (2010)
The genealogy of Maria de Aguilar: evidence of admixture in the early Spanish Colony in Costa Rica. During long time, historians and genealogists have interpreted that the elite that emerged during the Spanish Conquest was almost exclusively European. We reconstructed a deep matrilineal genealogy which includes recent Costa Rican ex-presidents and religious authorities back to their ancestors at the early 17th century, and compared their historic ethnic affinities with genetic mitochondrial evidence of some living descendents. The observed DNA lineage has an Amerindian ancestry. Such results point out that an Amerindian gene flow had occurred into the Spanish group during the first generations of colonial society. This conclusion do not support the current idea that the Spanish elite avoided interethnic marriages.